Sistem Informasi Testimoni Menggunakan Metode Fuzzy Associative Memory Berbasis WEB - Baqiyatur Rahma; Muhammad Fakhriza (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
In running a business, every company must provide good service to customers, because satisfactory service is very much needed to increase sales figures. However, building a sense of customer satisfaction is not that easy, it takes time to build it. Kaf Fragrance Shop, a shop engaged in the perfume sector, does not yet have a system to analyze customer testimonials effectively as a determining factor, so the store cannot identify customer needs. The purpose of creating this system, researchers want to evaluate customer satisfaction assessments by applying the FAM method or fuzzy associative memory to analyze how satisfied consumers are with the service provided by Kaf Fragrance. The FAM method was chosen because it can handle the uncertainty and ambiguity of data obtained from the questionnaire. The calculation is carried out from the questionnaire given which will later be calculated using the FAM method and the results will be classified using the defuzzification method which is carried out using the winner take all method or taking the largest value. The findings from the study are designed for assisting Kaf Fragrance elevating service quality and strengthening initiatives to improve customer satisfaction.